The Implementation Of The Kanban System To Improve The Effectiveness Of Production Processes In The Food Industry - Gayuh Lemadi (Baut Dan Manufaktur, 2023)
The Kanban system is an information system approach that jointly controls the amount of material in each production process. In preparing raw materials for the biscuit production process, it turns out that there are still often differences when shipping raw materials from inventory to production which results in a buildup of raw materials in production. One way to overcome the problem of differences in raw material delivery is to design a Kanban system in the production process. The purpose of this study is to reduce the difference in raw materials that occur by designing Kanban in the biscuit production process and measuring the effectiveness of Kanban in the biscuit raw material demand process. The results of Kanban design obtained 3 processes in the form of production planning design, pull Kanban design, and production Kanban design. Measurement of the effectiveness of Kanban is carried out after the implementation of Kanban, and results are obtained where before the delivery of Kanban there is a difference in the process of shipping raw materials, where for raw materials that often experience differences, namely BFLO18 with an average difference of 16% per month, then BGUL07 with an average difference of 24% per month and BFAT13 with an average difference of 29% per month. After implementation using the Kanban system, the difference in raw material delivery is 0%, or it can be said that there is no difference. When the Kanban system has begun to be implemented continuously, training will be carried out to provide an understanding of the work process of the Kanban system created and the preparation of SOP (Standard Operating Procedures) on the implementation of the Kanban system.